Hepatitis B - Rodrigo, Luis (IntechOpen, 2022)
Current pharmacologic therapies for chronic hepatitis B virus (HBV) infection allow viral suppression and normalization of the liver enzyme alanine aminotransferase (ALT) and prevent liver disease from progressing. The currently available antiviral therapies very rarely lead to a functional cure. Thus, the future of a cure for HBV lies in triple combination therapies with concerted action on replication inhibition, antigen reduction, and immune stimulation. This book reviews the mechanisms and pathogenesis of HBV, as well as discusses current and potential future treatments.